2015
DOI: 10.7287/peerj.preprints.1509v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pest suppression by ant biodiversity is modified by pest biodiversity

Abstract: Agroecosystems are often complex ecosystems with diverse food webs. Changes in food web complexity may have important context-dependent consequences for pest control strategies. The success of predator introductions to suppress pests may depend on the diversity of pests. For crops with diverse pest assemblages, it is hypothesized that diverse predator communities are needed to suppress diverse pest assemblages below damaging levels. In this study, we compare the ability of ant predator monocultures and polycul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Finally, it has been shown that several ESs provided by social insects are enhanced by higher biodiversity. For example, the biological control service provided by ants depends on the number of species both of pests and ant predators (Philpott, Pardee & Gonthier, 2012; Wielgoss et al ., 2014; Gonthier, Kuesel & Perfecto, 2015). While species richness does not necessarily affect the diversity of ESs performed by social insects, it can increase ES magnitude, stability, and resilience to future disturbances (Houadria et al ., 2016; Arnan, Molowny‐Horas & Blüthgen, 2019).…”
Section: Interaction Of Services Provided By Social Insects With Envimentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it has been shown that several ESs provided by social insects are enhanced by higher biodiversity. For example, the biological control service provided by ants depends on the number of species both of pests and ant predators (Philpott, Pardee & Gonthier, 2012; Wielgoss et al ., 2014; Gonthier, Kuesel & Perfecto, 2015). While species richness does not necessarily affect the diversity of ESs performed by social insects, it can increase ES magnitude, stability, and resilience to future disturbances (Houadria et al ., 2016; Arnan, Molowny‐Horas & Blüthgen, 2019).…”
Section: Interaction Of Services Provided By Social Insects With Envimentioning
confidence: 99%
“…While species richness does not necessarily affect the diversity of ESs performed by social insects, it can increase ES magnitude, stability, and resilience to future disturbances (Houadria et al ., 2016; Arnan, Molowny‐Horas & Blüthgen, 2019). In an artificial predator community with three ant species, pest suppression was higher than in a community with only one predator ant species; additionally, pest diversity reduced the efficiency of a single predator species at suppressing pest damage but did not limit multiple‐predator communities (Gonthier, Kuesel & Perfecto, 2015). Ants reduced damage caused by coffee pests in landscapes with high forest cover within a 2 km radius, where biodiversity is higher (Aristizábal & Metzger, 2019).…”
Section: Interaction Of Services Provided By Social Insects With Envimentioning
confidence: 99%